(untitled) (Scholars’ Journal, 2020)
This study examined the effect of using GeoGebra software on students’ achievement in the case of limit concepts at university level. The instruments used in this study were GeoGebra software, traditional teaching method, and Mathematics Achievement Test (MAT) taken to get the required information. A quasi-experimental design was used and the GeoGebra software introduced in teaching of the limit concept of Complex Analysis among twenty-nine students of section B and traditional teaching method introduced among thirty-one students of section A of the second semester of Master’s in Mathematics Education. After the pre-test, the control group students had been taken the limit concept and related problem in a traditional method and the experimental group students toughed the same content with interactive worksheets by using GeoGebra software. After five hours of lecture in both groups, the standardized MAT (2) was applied for the post-test to the students of both groups. The gathered quantitative data were analyzed by using SPSS 26 version of the scores of sixty students on both groups. As a result, the findings of the research showed that the pre-test scores of students in both groups were insignificant differences. But the pre-test and post-test scores of students in the experimental group and post-test scores of students in both groups were significant differences. The result showed that students were found more interactive in teaching through GeoGebra software and have a positive effect on students’ achievement on the limit concept.